Novel R225C variant identified in the HGD gene in Jordanian patients with alkaptonuria - Nesrin R. Mwafi; Dema A. Ali; Raida W. Khalil; Ibrahim N. Alsbou'; Ahmad M. Saraireh (AIMS Molecular Science, 2021)
Alkaptonuria (AKU) is a rare metabolic disease which is inherited as an autosomal recessive trait. It is characterized by the accumulation of homogentisic acid over time in various tissues of the body particularly connective tissues. This genetic disease is caused by mutation of the Homogentisate 1,2-dioxygenase (HGD) gene which encodes for enzyme essential for the catabolism of phenylalanine and tyrosine. The aim of the present study is to investigate variant types in Jordanian patients with alkaptonuria. Genomic DNA was extracted from whole blood samples of the participated AKU family members (n = 23). The 14 exons of HGD gene for the proband were amplified using specific PCR primers. The sequenced data were analysed and the pathogenicity of the identified variants were predicted using the online bioinformatics programs: PolyPhen2, SIFT and Mutation taster. The analysis showed that the proband was compound heterozygous for the missense mutations A122V and R225C found within E6 and E10, respectively. R225C variant is novel and the genotyping of the family members indicated that HGDA122V and HGDR225C alleles were fully segregated. Moreover, the cousins of the proband who are AKU patients inherited the homozygous pattern of the novel mutation. This study extends the pathogenic mutations spectrum of the HGD gene. It identified the novel mutation R225C and at the same time confirmed the high prevalence of the founder mutation A122V in Jordanian AKU patients.